Systematic Literature Review: Why Design and Technology Teachers Need to be Competent? - Mohd Bohari, Normila; Hatib Bin Musta’amal, Aede; Mohamad, Norliza; Suhaini, Mazlili; Ahmad, Khalidah (International Journal of Psychosocial Rehabilitation, 2020)
In Malaysia, the primary school life skills curriculum began in 1983. However, the demands of globalization and the need to produce knowledge workers have brought about significant changes to the curriculum. The Malaysian Education Ministry has created a new curriculum to integrate the education system in line with the aspiration of producing students with creative and critical thinking skills. The Malaysian Education Development Plan (2015-2025), which guides teachers, also outlines the educational needs of students to meet the challenges of life in the future. Thus, the life skills curriculum was replaced with the subject of design and technology. This review study aims to identify (1) the importance of competence for teachers’ Design and Technology (DT) and (2) the implications of the capability for teachers’ Design and Technology in the technical and vocational education system in the Malaysian context. A total of 13 document articles identified to discuss were retrieved from 2010 to 2019. All the items uploaded from the e-journal system provided by the university were used to identify the themes in previous studies. While PRISMA will be used to determine which research journal is appropriate to be selected and has empirical data. The results of this systematic review included students achievement, technology, quality teachers, professional development, lifelong learning, and learning support. This review studies recommended teacher-to-mastery in lifelong learning skills to develop their competency and expertise. Meanwhile, this study expects to assist the Ministry of Education and design and technology teachers in determining their competencies in performing school tasks.